2018
DOI: 10.1097/hp.0000000000000788
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low-level Ionizing Radiation on Cell Death During Zebrafish Embryonic Development

Abstract: Ionizing radiation (IR) has been linked to multiple types of cellular responses, but its effects on developing organisms are still poorly understood. The authors investigated whether zebrafish embryos exhibit differential responses relative to IR dose and developmental age at time of exposure. Early-stage zebrafish embryos were exposed to different levels of gamma radiation and then, at varying points after irradiation, assayed for morphological defects and levels of cell death. To quantify in vivo cellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, our measurements detected a notable reduction in body length, which suggests spinal cord curvature and growth delay. It is well known that different radiation qualities cause developmental deteriorations (41)(42)(43)(44), but only a few studies measured the degree of spinal curvature (19,20) and confirmed a linear dose dependent increase in severity on the fourth dpi at a dose level of 10 Gy or higher. Sayed and Mitani (45) showed spinal cord abnormality (body curvature) in the embryos of fish (Medaka) even after exposure to UV-A irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our measurements detected a notable reduction in body length, which suggests spinal cord curvature and growth delay. It is well known that different radiation qualities cause developmental deteriorations (41)(42)(43)(44), but only a few studies measured the degree of spinal curvature (19,20) and confirmed a linear dose dependent increase in severity on the fourth dpi at a dose level of 10 Gy or higher. Sayed and Mitani (45) showed spinal cord abnormality (body curvature) in the embryos of fish (Medaka) even after exposure to UV-A irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of bystander cell damage are as follows: On the one hand, ionizing radiation can directly cause DNA damage and cell death. On the other hand, radiation can indirectly promote cellcycle arrest, cell senescence, necrosis, or apoptosis through excessive oxidative stress and inflammation [12,32], which eventually leads to tissue microenvironment destruction and functional disorder [33]. During the treatment of head and neck cancer, sensorineural hearing loss is one of the "radiation-induced bystander effects".…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that the cochlear ribbon synapse is very sensitive to ionizing radiation, and this pathological change can occur in the acute phase after irradiation [11]. Radiation-induced tissue cell death is confirmed with the generation of ROS and the consequent activation of caspase, inflammation, apoptosis [12], and/or necrosis [13]. The biological functions of the body's immune system are diverse.…”
Section: Introductionmentioning
confidence: 98%